NanoSIMS and EPMA dating of lunar zirconolite - Nian Wang; Qian Mao; Ting Zhang; Jialong Hao; Yangting Lin (Progress in Earth and Planetary Science, 2021)
Abstract Zirconolite is a common Zr-rich accessary mineral in mafic rocks. It is also an ideal U–Pb/Pb–Pb chronometer because it commonly contains high U content (mostly 0.1–10 wt%) and negligible initial Pb. However, zirconolite is usually very small (e.g., ~ 1 μm in width) in lunar rocks, requiring a high spatial resolution analysis. We analyzed a single, large (25 μm × 20 μm) grain of zirconolite in lunar meteorite NWA 4485 using Pb–Pb dating by NanoSIMS and U–Th–Pb dating by EPMA. The resultant U–Th–Pb age is 4540 ± 340 Ma (2σ) with a spatial resolution of 1.3 μm. The Pb–Pb age by NanoSIMS is 4348.5 ± 4.8 Ma (2σ) with a spatial resolution of ~ 2 μm, consistent with the age of 4352 ± 10 Ma and 4344 ± 14 Ma reported in the same meteorite and its paired meteorite NWA 4472. Although U–Th–Pb age is somewhat older, it still includes the NanoSIMS results within the analytical uncertainty. This work demonstrates the potential application of the combined EPMA dating and REE analysis of lunar zirconolite, with the benefits of high spatial resolution, non-destructive, and readily accessibility of the instrument. The precision of the EPMA dating (7.6%, 2σ) can be improved by increasing the counting time for Pb, U and Th. We expect to apply this EPMA technique for a quick and non-destructive age survey and geochemical study of zirconolite grains from the lunar mare basalts newly returned by Chang’E-5 mission which landed on a very young (1.2–2.0 Ga by crater-counting chronology) basalt unit in Procellarum KREEP Terrain.